2005
DOI: 10.1007/s00268-005-7760-x
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐controlled Dietary Schedule Improves Clinical Outcome after Gastrectomy for Gastric Cancer

Abstract: Although studies have shown that early oral feeding after abdominal surgery is feasible, the optimal dietary schedule has not been established. This study was conducted prospectively to compare the clinical outcome of patient-controlled dietary schedule with that of conventional dietary schedule after gastric resection for early cancer. Patients in the patient-controlled diet (PC) group (n = 53) received a solid diet on demand; patients in the conventional regimen (CR) group (n = 50) received a solid diet from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 23 publications
3
50
0
Order By: Relevance
“…In 2004, Suehiro et al [13] first reported early oral feeding within 48 h of gastrectomy reduced hospital stay as compared with conventional postoperative fasting; postoperative morbidities and mortalities, including nausea, vomiting, anastomotic leakage, and wound infections were similar in their two groups. In 2005, Hirao et al [12] introduced the ''patient-controlled diet schedule'' for patients that undergo gastrectomy, according to which a solid diet is supplied on patient demand from the third postoperative day. As compared with a fixed diet regimen requiring that a solid diet be started on the 10th postoperative day, patients showed shorter hospital stays and no increase in morbidity or mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2004, Suehiro et al [13] first reported early oral feeding within 48 h of gastrectomy reduced hospital stay as compared with conventional postoperative fasting; postoperative morbidities and mortalities, including nausea, vomiting, anastomotic leakage, and wound infections were similar in their two groups. In 2005, Hirao et al [12] introduced the ''patient-controlled diet schedule'' for patients that undergo gastrectomy, according to which a solid diet is supplied on patient demand from the third postoperative day. As compared with a fixed diet regimen requiring that a solid diet be started on the 10th postoperative day, patients showed shorter hospital stays and no increase in morbidity or mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, proponents of traditional postoperative fasting after gastrectomy often cite concerns of anastomosis safety and aspiration pneumonia. Recently, small retrospective studies [12,13] and a randomized controlled trial [14] have found that early oral nutrition after gastrectomy is both beneficial and feasible. However, few studies have examined an immediate oral nutrition starting on the first postoperative day after gastrectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Dietitians, clinicians, and nurse clinicians are all involved. Prior to surgery, patients receive a high-protein diet with supplements whenever possible, as early satiety and malnutrition are common after gastrectomy [13]. Upon discharge from surgery, detailed counseling and visual information on diet are given to patients and their families.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have shown that early oral feeding is feasible after gastrectomy, the optimal dietary schedule has not been established [14,15]. Traditionally, postoperative oral intake after abdominal surgery was slowly and carefully introduced, due to anstomotic leakage and postoperative paralytic ileus.…”
Section: Discussionmentioning
confidence: 99%